The Magic Fan - Baker, Keith 1953- (San Diego : Harcourt Brace Jovanovich, 1989)
Despite the laughter of his fellow villagers, Yoshi uses his building skills to make a boat to catch the moon, a kite to reach the clouds, and a bridge that mimics the rainbow.
Keywords: Toy and movable books -- Specimens